Friedrich list: nacionalismo e cosmopolitismo na integração dos estados alemães - Oliveira, Flávio dos Santos (2017)
The thesis proposes a historical reconstruction of the economic thought of Friedrich List in order to highlight his contribution to the economic and political integration of the German States. The research was organized in four chapters. In the first one, the disintegration factors concerning the German power structure up to the nineteenth century, as well as the process of re-signification of the concept of nation during the Sattelzeit, are brought to the fore. In the second, besides List's formation as an intellectual and bureaucrat, his activity in favor of consolidating the American System of Political Economy is emphasized, as well as the influence of Historicism and German Idealism in the elaboration of his historical method. In the third chapter, certain fundamental characteristics of the German Cameralism movement are stressed, and a study about the diffusion process of classical liberal orthodoxy in the German domains is presented. Also, a set of structural changes that culminated in the industrialization of Germany is pointed out. Along with that, not only the positive effects of the agrarian reform and the Zollverein are discussed, but also it is underlined how List's national railway system accelerated this process. The last chapter analyzes the influence of the Enlightenment and its ideal of progress in List's economic thinking. There follows an interpretation of the systematic scheme implicit in the key work of the German economist. The implications of List’s concept of Deutschland and his theory of international trade are discussed in the sequence. Lastly, List's legacy in the twentieth century is appreciated by a study of the activities undertaken by the Friedrich List-Gesellschaft (Friedrich List Society (1925-1935) and the List-Gesellschaft (List Society). Particularly regarding the institution of the European Union. The economic problems currently faced by the European Union are analyzed on the basis of List's teachings, which asserted that free competition only promotes the well-being of all participating countries if they share a similar stage of development of their productive forces.